Prognostic factors and survival in patients with metastatic or recurrent carcinoma of the uterine cervix. Issue 4 (1st June 2003) - Eralp, Y.; Saip, P.; Sakar, B.; Kucucuk, S.; Aydiner, A.; Dincer, M.; Aslay, I.; Topuz, E.
Abstract : The aim of this study is to identify the impact of various prognostic factors on survival in patients with recurrent carcinoma of the uterine cervix. Fifty-two patients who were treated with platinum-based chemotherapy for recurrent or metastatic disease were retrospectively evaluated. Twenty-seven patients (90%) had received pelvic radiation as primary treatment. Out of 45 evaluable patients, two (4.4%) had complete response (CR), three (6.7%) had a continuous CR after additional surgical treatment and irradiation. Five patients (11.1%) had partial response (PR). The majority of patients had progressive response to treatment (22 patients, 48.9%). After a median follow-up period of 19 months, 31 patients (60%) had died. Progression-free survival after initial diagnosis was observed to have a significant association with response to chemotherapy for recurrent disease (Fisher two-sided P = 0.027). The median survival duration for relapsed disease was 11.8 months. Those with a longer disease-free interval (8 months vs. ≤ 8 months) from initial diagnosis to first recurrence and reponse to chemotherapy had a tendency for a longer survival duration after relapse by univariate analysis. Multivariate analysis revealed that progressive response to chemotherapy ( P = 0.002, HR = 4.6) and recurrence within the previously irradiated field ( P = 0.04, HR = 2.7) were significant independent prognostic factors for a shorter time to progression after recurrence. Furthermore, advanced stage at presentation ( P = 0.001, HR = 3.0) and a short disease-free interval after primary treatment (<8 months, P = 0.003, HR = 3.4) were determined as independent prognostic factors with a significant negative influence on progression-free survival and overall survival from initial diagnosis, respectively. The use of toxic and expensive combinations for the treatment of recurrent cervical cancer patients should be well balanced against potential hazards. Based on our data, less toxic regimens would be more feasible in patients who present with advanced disease at initial diagnosis, or those that experience recurrence within the previously irradiated field after a progression-free interval of less than 8 months.